2019
DOI: 10.1097/sga.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

Aminotransferase Ratio Is a Useful Index for Hepatosteatosis in Children and Adolescents

Abstract: Nonalcoholic fatty liver disease (NAFLD) and childhood obesity are emerging global health issues. The aim of this study was to identify a simple predictor of NAFLD in children and adolescents. This community-based study was conducted from December 2012 to September 2013 in Taiwan and included 1,222 children between 10 and 19 years of age. After excluding alcohol consumption and hepatic-related lesions, NAFLD was diagnosed according to sonographic criteria. Potential confounding factors (including age, gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Similar results have been reported once in China [22]. In a recent study, Lu et al also found a correlation of the ALT/ AST ratio with NAFLD risk in 1222 adolescents and children [25], which was similar to the results of age stratification in this research. Although these studies emphasize the correlation of the ALT/AST ratio with NAFLD risk, they were all cross-sectional in design, and the sample sizes were relatively small (1222, 1354, 6926 and 10,724).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results have been reported once in China [22]. In a recent study, Lu et al also found a correlation of the ALT/ AST ratio with NAFLD risk in 1222 adolescents and children [25], which was similar to the results of age stratification in this research. Although these studies emphasize the correlation of the ALT/AST ratio with NAFLD risk, they were all cross-sectional in design, and the sample sizes were relatively small (1222, 1354, 6926 and 10,724).…”
Section: Discussionsupporting
confidence: 92%
“…Presently, there are limited studies that have reported on the association of the ALT/AST ratio with NAFLD risk. Only a few cross-sectional studies have found a positive correlation of NAFLD risk with the ALT/AST ratio [22][23][24][25]. Nevertheless, the association of the ALT/AST ratio with NAFLD in nonobese individuals remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Lu CW, et al, (24), have conducted a study investigating the Aminotransferase index in children and adolescents diagnosed with NAFLD(+) by USG. The study has found that participants with a higher index had a 2.19 times higher risk of developing NAFLD (95% CI: 1.24-3.87; p = 0.007) (24).…”
Section: Discussionmentioning
confidence: 99%
“…Lu CW, et al, (24), have conducted a study investigating the Aminotransferase index in children and adolescents diagnosed with NAFLD(+) by USG. The study has found that participants with a higher index had a 2.19 times higher risk of developing NAFLD (95% CI: 1.24-3.87; p = 0.007) (24). In our study, we examined obese adolescents, who had been diagnosed with NAFLD by MRI, and found that the Aminotransferase index was signi cantly higher in the NAFLD (+) group.…”
Section: Discussionmentioning
confidence: 99%
“…These markers often include anthropometric indices [22][23][24], serum lipid-associated indices [25,26], aminotransferases [27], or the markers composed of them. Bedogni et al developed a simple scoring system called the fatty liver index (FLI) as a predictor of fatty liver disease [28], and several studies have reported that NAFLD assessed by FLI was well-correlated with hepatic steatosis using abdominal ultrasonography in a general population [29,30].…”
Section: Introductionmentioning
confidence: 99%